C'est quoi ce travail? - Joulé, Luc.; Jousse, Sébastien (France : Shellac, 2015)
The film follows the routines of employees of a car part manufacturing company that produces 800,000 parts per day. It traces the resonations between the factory workers and the composer Nicolas Frize, whose compositions are inspired by factory and workshop soundscapes.
Verzio Film Festival Submission
Keywords: Documentary films